102k views
2 votes
Plz help me!!!!!!! 

Instructions: Select the correct answer from each drop-down menu. When p2 – 4p is subtracted from p2 + p – 6, the result is . To get p – 9, subtract from this result.



 -3p-6.       4p+3
5p-6           4p-15
4p+6.          4p+12

User Jose Reyes
by
4.8k points

1 Answer

3 votes
When p2 – 4p is subtracted from p2 + p – 6, the result is:
p2+p-6-(p2-4p)=p2+p-6-p2+4p=5p-6

To get p – 9, subtract from this result x:
5p-6-x=p-9
Solving for x:
5p-6-x+x-p+9=p-9+x-p+9
4p+3=x
x=4p+3

Answer:
1) When p2 – 4p is subtracted from p2 + p – 6, the result is 5p-6
2) To get p – 9, subtract from this result 4p+3
User Sanjeev Dhiman
by
5.9k points